Respons(A)bility: Weaving Words of Responsibility Through Story - Belanger, Mariel (Percées)

(untitled) (Société québécoise d'études théâtrales (SQET), 2023)
This AuNTIe paper calls for better ways of being and doing in academe than the status quo practices across universities. Mad Native Auntie sits you down for a class in understanding why Indigenous ways of knowing are not tools like interview or survey for academics to colonize as free-for-all methodological use. Auntie addresses the demoralization that occurs when the Indigenous “other” is made teacher of pan-Indigenous epistemology. I discuss my understanding of duty-of-care through research, taking precautions to predict what could be happening for others when applied to the understanding of performance ethnography as course work.